RESOURCE USE AND QUALITY OF CARE IN AN URBAN STROKE UNIT. Issue 11 (9th October 2013) - Boyle, Jennifer; Casey, Helen; Doyle, Claire; Walters, Matthew
Abstract : Background: Stroke is the third most common cause of mortality and the most common cause of disability worldwide. It has been consistently shown that patients placed on acute stroke units (ASU) have significantly better outcome measures. We attempted to gain a better understanding of the benefits of the stroke unit by following stroke patients within and out with ASU, Western Infirmary Glasgow. Furthermore, the efficiency of bed management within ASU was assessed. Methods: Over a 3 week period we investigated all patients under the care of the stroke team. There were 3 groups: stroke patients within ASU; medical boarders in ASU; and stroke patients boarded out with ASU. 29 stroke patients in ASU and 18 stroke patients boarded out were compared based on a range of parameters. At 11am on each weekday a snapshot view of all three groups was performed in order to assess bed management. Results: Stroke patients within ASU were shown to have significantly less time to CT brain (p<0.0001), shorter time to therapist review (p=0.0447), more blood pressure (p=0.0243) and Glasgow Coma Score (p=0.0033) measurements in their first 24 hours of admission than stroke patients boarded out with ASU. Age, sex, DEPCAT score and time to consultant review were found to be not significant between the two groups of stroke patients. Conclusion: Better outcome measures in ASU could be attributed to the differences between the groups of stroke patients. Prompt therapist input and frequent nursing observations have long been considered to be imperative in the success of ASU; our findings wholly support this and highlight the importance of the multidisciplinary approach. The snapshot data revealed that bed capacity on ASU was sufficient for the number of stroke patients. However capacity was not being utilised efficiently as non–stroke medical boarders occupied beds consistently whilst stroke patients were boarded out to other wards.